Stable T-bet+GATA-3+ Th1/Th2 hybrid cells arise in vivo, can develop directly from naive precursors, and limit immunopathologic inflammation - Peine, Michael; Rausch, Sebastian; Helmstetter, Caroline; Fröhlich, Anja; Hegazy, Ahmed N.; Kühl, Anja A.; Grevelding, Christoph; Höfer, Thomas; Hartmann, Susanne; Löhning, Max (PLoS biology, 2013)
Differentiated T helper (Th) cell lineages are thought to emerge from alternative cell fate decisions. However, recent studies indicated that differentiated Th cells can adopt mixed phenotypes during secondary immunological challenges. Here we show that natural primary immune responses against parasites generate bifunctional Th1 and Th2 hybrid cells that co-express the lineage-specifying transcription factors T-bet and GATA-3 and co-produce Th1 and Th2 cytokines. The integration of Th1-promoting interferon (IFN)-γ and interleukin (IL)-12 signals together with Th2-favoring IL-4 signals commits naive Th cells directly and homogeneously to the hybrid Th1/2 phenotype. Specifically, IFN-γ signals are essential for T-bet+GATA-3+ cells to develop in vitro and in vivo by breaking the dominance of IL-4 over IL-12 signals. The hybrid Th1/2 phenotype is stably maintained in memory cells in vivo for months. It resists reprogramming into classic Th1 or Th2 cells by Th1- or Th2-promoting stimuli, which rather induce quantitative modulations of the combined Th1 and Th2 programs without abolishing either. The hybrid phenotype is associated with intermediate manifestations of both Th1 and Th2 cell properties. Consistently, hybrid Th1/2 cells support inflammatory type-1 and type-2 immune responses but cause less immunopathology than Th1 and Th2 cells, respectively. Thus, we propose the self-limitation of effector T cells based on the stable cell-intrinsic balance of two opposing differentiation programs as a novel concept of how the immune system can prevent excessive inflammation.
Im Titel ist das "+"-Zeichen jeweils hochgestellt
Gesehen am 03.01.2022